Diagnosis of Hereditary TTP Caused by Homozygosity for a Rare Complex ADAMTS13 Allele After Salmonella Infection in a 43-Year-Old Asylum Seeker - Wendt, Ralph; Kalbitz, Sven; Otto, Felix; Falter, Tanja; Beige, Joachim; Rossmann, Heidi; Lämmle, Bernhard (Frontiers in Medicine, 2021)
A 43-year-old Armenian patient was diagnosed with salmonella infection and thrombotic microangiopathy (TMA). The clinical course was benign with resolution of all laboratory alterations after antibiotic treatment. Constantly deficient ADAMTS13 activity without ADAMTS13 inhibitors and evidence of homozygosity for a rare complex ADAMTS13 allele led to the diagnosis of congenital thrombotic thrombocytopenic purpura (cTTP). Half-life of ADAMTS13 after plasma infusion was calculated (27,6h) and double blinded plasma infusion as well as ergometric exercise with and without prior plasma infusion undertaken to investigate suspected smoldering TTP activity.